Boosted charge transfer in porphyrin and zinc phthalocyanine co-functionalized graphene oxide nanohybrids toward improved optical limiting and H2 evolution. (March 2021) - Wang, Aijian; Shen, Xiaoliang; Wang, Qi; Cheng, Laixiang; Zhu, Weihua; Shang, Danhong; Song, Yinglin
Abstract: In this contribution, we disclose that reaction of the tetrakis(4-aminophenyl)porphyrin (TPP) and tetraaminophthalocyanine (ZnPc) with GO gives a donor-acceptor type hybrid material (TPP-GO-ZnPc). An analysis of the structure-property relationships in redox and optoelectronic performances has been performed by comparing their photophysical spectroscopy and electrochemistry. The results reveal that the resultant TPP-GO-ZnPc ternary nanohybrid exhibits enhanced optical limiting and HER response in comparison with those of TPP-functionalized GO (TPP-GO), ZnPc-functionalized GO (ZnPc-GO) and their constituents, stemming from a combination of mechanisms and more effective charge transfer effect. The strong electronic interactions and charge transfer effect within TPP-GO-ZnPc has been investigated by the UV–Vis absorption, photocurrent response, fluorescence and electrochemical impedance spectrum. Highlights: TPP-GO-ZnPc ternary nanohybrid was prepared. The ternary nanohybrid exhibits enhanced optical limiting and HER. The improved performance is assigned to a combination of mechanisms.